The Impact of Financing Digitalization on MSME Operational Effectiveness: The Mediating Role of Innovation, Digital Infrastructure, and Fintech - Tri Dharma Sipayung (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to examine the influence of financing digitalization on the operational effectiveness of Micro, Small, and Medium Enterprises (MSMEs), mediated by product innovation, digital infrastructure, and financial technology in Medan City. Utilizing a quantitative descriptive approach, the research employed Structural Equation Modeling (SEM) with SMART PLS 3.0 to analyze data from 100 MSMEs selected through simple random sampling from a population of 38.343 units in Medan City in 2023. Data were gathered through questionnaires, observations, and secondary sources, ensuring strong validity and reliability. The findings reveal that financing digitalization significantly improves MSME operational effectiveness both directly (T=6.233, p<0.001) and indirectly through product innovation (T=4.112, p=0.003), digital infrastructure (T=3.347, p=0.001), and financial technology (T=5.534, p=0.002). These mediating variables contribute to enhanced efficiency by simplifying transaction processes, strengthening infrastructure reliability, and automating financing operations. The study highlights the critical importance of adopting digital financing solutions within MSMEs to remain competitive. It also emphasizes the role of policymakers in facilitating this transformation by investing in digital infrastructure and implementing comprehensive digital literacy programs to foster a sustainable and inclusive digital economy.